2019
DOI: 10.3390/cells8070709
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Regulates Indoleamine-2,3-dioxygenase-Dependent Cross-Talk between Colon-Infiltrating Dendritic Cells and T Regulatory Cells and May Represent a Valuable Biomarker for Monitoring the Progression of Ulcerative Colitis

Abstract: Galectin-3 regulates numerous biological processes in the gut. We investigated molecular mechanisms responsible for the Galectin-3-dependent regulation of colon inflammation and evaluated whether Galectin-3 may be used as biomarker for monitoring the progression of ulcerative colitis (UC). The differences in disease progression between dextran sodium sulphate-treated wild type and Galectin-3-deficient mice were investigated and confirmed in clinical settings, in 65 patients suffering from mild, moderate, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
1
18
1
Order By: Relevance
“…For instance, Simovic Markovic et al (2016) showed an important pro-inflammatory role that Gal3 plays in events that accompany UC, while other authors found that Gal3 reduces the colon inflammation in animal models of experimental colitis (Tsai et al, 2016); (Lippert et al, 2015). More recently, it has been shown that the effects of Gal3 deletion vary as colon inflammation progresses since Gal3 may direct the polarization of colonic macrophages towards inflammatory or anti-inflammatory phenotype (Volarevic et al, 2019). Moreover, Gal3 seems to be involved in processes that maintain the barrier in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Simovic Markovic et al (2016) showed an important pro-inflammatory role that Gal3 plays in events that accompany UC, while other authors found that Gal3 reduces the colon inflammation in animal models of experimental colitis (Tsai et al, 2016); (Lippert et al, 2015). More recently, it has been shown that the effects of Gal3 deletion vary as colon inflammation progresses since Gal3 may direct the polarization of colonic macrophages towards inflammatory or anti-inflammatory phenotype (Volarevic et al, 2019). Moreover, Gal3 seems to be involved in processes that maintain the barrier in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell infiltration is an important biomarker of inflammation. DSS feeding resulted in an increased production of macrophage-derived cytokines in BALB/c mice [ 26 ]. We also found macrophages accounted for the highest proportion of immune infiltrating cells in the DSS-induced UC model (Figures 5(a) and 5(b) ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that both total absence (Lgals3 −/− BALB/c mice) or reduction of galectin-3 in the gut-liver axis induced by milk supplementation increased atypical behaviors. The role of galectin-3 as immunomodulatory factor in the gut and liver has been attracted the attention of specialists 15,20 .…”
Section: Discussionmentioning
confidence: 99%